Penerapan Aplikasi Administrasi Microsoft Office Pada Para Operator Pendidikan Anak Usia Dini (PAUD) di Kecamatan Syiah Kuala Kota Banda Aceh - Zainuddin; Saiful; Masri; Putra, T. Edisah; Machmud, M. Nizar; Suhaeri; Akhyar; Suriadi; Devi Sara, Ira; Malahayati, Nurul (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
Early childhood education (PAUD) is very important to prepare an educated generation for the nation and state, and the role of early childhood educators (PAUD) is very important in the development of students. Educators need to go beyond traditional learning by providing learning innovations that utilize information technology, including the ability to master the latest information technology. The focus of the Community Service Program (PKM) is to improve   the quality of human resources (HR) of PAUD organizers in Syiah Kuala District, Banda Aceh Province in the field of information technology, so that they are able to support the management of learning and educational activities. In improving the quality of kindergarten teaching staff in the field of information technology is related to supervision management and making daily learning implementation plans (RPPH). With a system that allows teachers to quickly resolve administrative problems, it is hoped that they can use their time to further develop their knowledge and skills regarding PAUD administrative problems.